Numerical Simulation of the Effects of Wedge Subduction on the Lithospheric Thermal Structure and the Seismogenic Zone South of Chile Triple Junction - Guo, Changsheng; Sun, Pengchao; Wei, Dongping (Frontiers in Earth Science, 2021)
In contrast to common subduction, the young and thin part of the Antarctic Plate subducts first to the south of the Chile Triple Junction (CTJ), followed by the old and thick part, corresponding to wedge subduction. A finite element model was used to simulate the wedge subduction of the Antarctic Plate and to compare it to the slab subduction of the Nazca Plate. The results show that the CTJ is not only a wedge subduction boundary, but also an important factor controlling the lithospheric thermal structure of the overriding plate. The computed heat flow curves are consistent with the data observed near the trench of the two selected profiles. The different slab dips to the north and south of the CTJ are considered to be caused by wedge subduction: When the slabs are young and at the same age, the deep dip of the Antarctic slab is 22° smaller than the Nazca slab. Southward from the CTJ, the slab age of the wedge subduction increases, which leads to a larger slab dip, a colder slab, and a wider seismogenic zone. The effect of the slab age of wedge subduction on the focal depth is smaller than that of the convergence rate. A 4.8cm/yr difference in convergence rate of the wedge subduction results in an 11km difference in the width of the seismogenic zone and a 10km difference in the depth of the downdip limit. Among these controlling factors, the convergence rate plays a major role in the different focal depths south and north of the CTJ.